2013
DOI: 10.4137/oed.s12352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bevacizumab Injection before Vitrectomy on Intravitreal Hemorrhage in Pseudophakic Patients with Proliferative Diabetic Retinopathy

Abstract: We evaluated the effect of intravitreal bevacizumab (IVB) injection before pars plana vitrectomy (PPV) on intravitreal hemorrhage (VH) during and after vitrectomy for postoperative the first day and the first month in pseudophakic patients with proliferative diabetic retinopathy (PDR). This retrospective study was performed on 44 eyes of 44 patients who underwent vitrectomy for PDR. Patients were divided into PPV (n = 22 eyes) and PPV + IVB (n = 22 eyes) groups. Injection of bevacizumab (1.25 mg/0.05 mL) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…The reported prevalence of PDVH (occurring 1 or more weeks after surgery) is between 20% and 30%. [4,16] Many studies report that intravitreal anti-VEGF drugs administered before surgery can significantly reduce the probability of PDVH [1,16,28] ; however, other studies have contradicted these results and shown that these drugs fail to prevent PDVH. [23,29,30] Although definitive conclusions cannot be drawn, all studies [23,29,30] have shown that injection of anti-VEGF drugs (Bevacizumab and Ranibizumab) is helpful for limiting fibrovascular proliferation before vitrectomy, makes surgery easier, decreases surgical time, and reduces the frequency of endodiathermy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of PDVH (occurring 1 or more weeks after surgery) is between 20% and 30%. [4,16] Many studies report that intravitreal anti-VEGF drugs administered before surgery can significantly reduce the probability of PDVH [1,16,28] ; however, other studies have contradicted these results and shown that these drugs fail to prevent PDVH. [23,29,30] Although definitive conclusions cannot be drawn, all studies [23,29,30] have shown that injection of anti-VEGF drugs (Bevacizumab and Ranibizumab) is helpful for limiting fibrovascular proliferation before vitrectomy, makes surgery easier, decreases surgical time, and reduces the frequency of endodiathermy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown intravitreal Bevacizumab (IVB) to be safe and effective in reducing the incidence of recurrent postoperative VH. [17,28,37] The IVB injection also does not carry the risk of an early temporary rise in IOP that is seen with the IVT injection. Both Bevacizumab and Ranibizumab have been reported to cause regression of neovascularization in eyes with active progressive PDR.…”
Section: Discussionmentioning
confidence: 99%
“…As an anti-VEGF agent, ranibizumab is an engineered, humanized, recombinant antibody fragment active against all VEGF-A isoforms and has a shorter half-life than other similar agents [ 3 ]. Increasing evidences showed that preoperative anti-VEGF treatment reduces the risk of intraoperative or postoperative bleeding in PDR patients and improves best corrected visual acuity (BCVA) [ 4 8 ]. Recently, we found that preoperative intravitreal injection of ranibizumab (IVR) for patients with severe proliferative diabetic retinopathy (PDR) contributed to a decreased risk of postoperative neovascular glaucoma [ 9 ], which is among the most serious postoperative complication of PDR.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that for less experienced surgeons, avoiding intra-operative bleeds may have a significant improvement on the total surgery time by providing a clearer view during surgery. The reduction in surgical time in patients receiving IVB before vitrectomy has also been reported by several authors 16,20,21. This is the consequence of less instrumentation requirement, clearer view during vitrectomy, reduced risk of creating iatrogenic breaks and easier dissection of membranes and decreased need of endolaser 12…”
Section: Discussionmentioning
confidence: 56%